Knockdown of Sfrp4 attenuates apoptosis to protect against myocardial ischemia/reperfusion injury - Wenhui Zeng; Yu Cao; Wanli Jiang; Ganjun Kang; Jie Huang; Songping Xie (Elsevier, 2019)
Secreted frizzled-related protein (Sfrp) 4 is a protein that involve in cardiac development and several cardiovascular diseases. However, the effect of Sfrp4 in mediating myocardial ischemia/reperfusion injury remains unknown. In this work, adenoviral (Ad)-shSfrp4 adenoviruses was used to knockdown of Sfrp4 in myocardium to examine the role of Sfrp4 in mediating myocardial I/R injury. Knockdown of Sfrp4 in mice attenuated myocardial I/R injury, as indicated by the decrease levels of lactate dehydrogenase and creatine kinase, and increment of ventricular function following I/R injury. Besides, knockdown of Sfrp4 led to a reduction in Bax, active caspase 3, and increase Bcl-2 and c-Myc in cardiac tissue. Knockdown of Sfrp4 lost its protection against I/R injury in mice infected with Ad-dn-AKT. In conclusion, knockdown of Sfrp4 in myocardium attenuated myocardial ischemia and reperfusion injury by AKT signaling pathway. Keywords: Sfrp4, Ischemia/reperfusion, AKT, Apoptosis